Study of Agung Sleman Mosque Minaret Construction Design: Errors and Solutions - Ala Ali Qasem Alraimi; Muhammad Ikhsan Setiawan; Adi Prawito (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study helps to solve the problem at the minaret of Agung Mosque which costs about (Rp16.000.000.000), located in Yogyakarta city, Indonesia, Sleman street, where its high sixty seven meters from the ground and it consists of fifty floors, where analyze and prove the safety of the minaret dome, replace the dome, repair the fallen parts from middle floors, and calculate the total cost of replacing the dome and repairing fallen parts of the minaret. This study proved that the existing design reinforcement of the dome is totally safe, estimated the total cost of solving the minaret problems which (Rp2, 281,873,633.54). Where the total costs of replacing the dome were (Rp2, 073,135,813), the total costs of fixing the damaged “fallen” parts of the middle floors were (Rp1, 294,762.24), and the total of the unexpected costs were (Rp207, 443,057.59)